Preclinical safety evaluation of levonadifloxacin, a novel anti‐methicillin‐resistant Staphyloccocus aureus benzoquinolizine fluoroquinolone by intravenous and oral administration. Issue 8 (22nd February 2022) - Nandanwar, Manohar; Kansagara, Atul; Gupta, Sangita; Patel, Anasuya; Patel, Muftedar Ahmed; Yeole, Ravindra; Thorve, Deepak; Patel, Mahesh
Abstract: Fluoroquinolone (FQ) antibacterials have drawn heightened attention from various international regulatory agencies due to their class‐specific side effects. Levonadifloxacin is a novel broad spectrum benzoquinolizine FQ active against methicillin‐resistant Staphyloccocus aureus (MRSA). Owing to FQ‐associated safety concerns, extensive preclinical safety pharmacology (central nervous system and cardiac safety) and toxicology studies (subacute repeat‐dose toxicity, genotoxicity, phototoxicity and chondrotoxicity) of levonadifloxacin were performed at relatively high doses. Intravenous (IV) and oral studies were conducted using WCK 771 (l ‐arginine salt of levonadifloxacin) and WCK 2349 (l ‐alanine ester prodrug of levonadifloxacin), respectively. Safety pharmacology studies following single dose revealed no adverse effects on central nervous system (including seizure) in mice and cardiovascular system (hERG and monkey telemetry). In repeat‐dose toxicity studies, except for IV bolus dosing related effects in rat (hyperactivity, mild convulsion, polypnoea and injection site irritation) and dog (emesis and salivation), no other adverse findings limiting the dosing duration were observed. No major biochemical, haematological, gross or histopathological changes suggestive of damage to vital organs were observed in either WCK 771‐ or WCK 2349‐treated groups. WCK 771 and WCK 2349 were found to be nongenotoxic; however, they showed weak phototoxicity that was comparable with levofloxacin. WCK 771 showed chondrotoxicity in the Beagle dog pups on repeat‐dose administration; however, the severity level was lower than ofloxacin. Overall, preclinical safety studies helped establish wider safety margin for WCK 771 and WCK 2349 that supports administration of higher therapeutic doses in humans by both IV and oral routes, thereby enabling safe anti‐MRSA treatment. Abstract : Levonadifloxacin, an anti‐MRSA fluoroquinolone (FQ) antibiotic exhibits good preclinical safety following repeat‐dose toxicity studies. It lacks seizure potentials in mice and is devoid of cardiovascular effects in monkey telemetry and hERG assay. It is non‐genotoxic, weakly phototoxic and chondrotoxic in comparison to other reference FQs.